Lecanicillium coprophilum–mediated green synthesis of zinc oxide nanoparticles displaying antimicrobial activity against important rice pathogens - Kheirel Anuar, Muhammad Salahudin; Khairuddin, Nur Hazwani; Zainal, Zaishazleen Shazwanie; Nazarudin, Muhammad Farhan; Azmai, Mohammad Noor Amal; Salleh, Annas; Che Abdullah, Che Azurahanim; Md Yasin, Ina Salwany; Yusof, Mohd Termizi (Taylor and Francis, 2025)
Spot and blight diseases are prevalent in the paddy sector, particularly in Malaysia, and are caused by the pathogens Burkholderia glumae and Curvularia lunata. To combat these issues, chemical pesticides, fungicides, and antibiotics are commonly used due to their affordability and ease of application. However, their excessive use has led to serious environmental issues, including groundwater pollution, soil contamination, and toxicity to non-target organisms. To address these concerns, nanotechnology, especially the “green synthesis” method, has recently gained attention. One approach uses metabolites from microbes as reducing agents to synthesize metal oxide nanoparticles, offering a more environmentally friendly alternative to conventional disease control methods. This study aims to explore the ability of a soil-derived fungal isolate to synthesize zinc oxide nanoparticles (ZnO-NPs) and to characterize the physicochemical properties and antimicrobial activity of the generated ZnO-NPs against paddy pathogens. In this study, a single fungal isolate capable of growing on potato dextrose agar (PDA) supplemented with 2 mM ZnSO4·7H2O was obtained from soil. The isolate, identified as Lecanicillium coprophilum, demonstrated the ability to synthesize ZnO-NPs. Characterization of the synthesized ZnO-NPs using various analytical techniques revealed distinct rod- and spherical shaped nanoparticles with a hexagonal wurtzite structure. Antimicrobial assessment showed that higher ZnO-NP concentrations led to greater inhibition of B. glumae and C. lunata. This study highlights the potential of green-synthesized ZnO-NPs as an eco-friendly alternative for managing paddy diseases.